Bibliometric Analysis of Green Finance and Sustainable Investment Strategies - Judijanto, Loso; Yoga, Tirta; Wijayanti, Indah Oktari (Westscience Press, 2024)
Green finance and sustainable investment strategies have gained significant attention as key mechanisms to address global environmental challenges and drive sustainable development. This study employs bibliometric analysis to explore the thematic, geographical, and temporal trends in research on green finance and sustainable investments, using data from the Scopus database. The findings reveal that central themes, such as